2017
DOI: 10.1016/j.resuscitation.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Delayed return of spontaneous circulation (the Lazarus phenomenon) after cessation of out-of-hospital cardiopulmonary resuscitation

Abstract: We observed that the Lazarus phenomenon is a real albeit rare event and can occur a few minutes after the cessation of out-of-hospital CPR. We suggest a 10-min monitoring period before diagnosing death. CPR guidelines should be updated to include information of the Lazarus phenomenon and appropriate monitoring for it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…1). All the references were retrospective case reports of which five [2,13,[23][24][25] described two patients, and one [26] described a series of five patients (Additional file 1: Table S1). Brief clinical details of the cases included in this review are reported in Additional file 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). All the references were retrospective case reports of which five [2,13,[23][24][25] described two patients, and one [26] described a series of five patients (Additional file 1: Table S1). Brief clinical details of the cases included in this review are reported in Additional file 2.…”
Section: Resultsmentioning
confidence: 99%
“…Although the biblical Lazarus rose from the dead without resuscitation attempts, there are no case reports of it occurring in someone who has died without CPR performed beforehand [9,33]. Almost all cases of autoresuscitation occurred after CPR following non-traumatic CA; there is only one report following traumatic CA [34] and four others associated with major haemorrhage [26,[35][36][37]. Therefore, it has been suggested that autoresuscitation is due to the medical interventions that were performed during resuscitation, but their effectiveness was delayed for some reason [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoresuscitation, also known as delayed return of spontaneous circulation (ROSC) or the Lazarus phenomenon, is the unassisted ROSC after cardiac arrest 1 . Autoresuscitation in people was first described in 1982; it is considered to be an exceptionally rare phenomenon, with a reported incidence of 5.95/1,000 in out‐of‐hospital cardiac arrest 2 . The authors of a meta‐analysis published in 2015 identified approximately 45 human cases that occurred after futile CPR or after life support was discontinued, and those patients were clinically dead for a range of seconds to 7 minutes before autoresuscitation occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the people experience this phenomenon have the same condition as Lazarus. Lazarus is a Syndrome with spontaneous circulation even in some people with unsuccessful cardiopulmonary resuscitation [3], [4], [5], [6].…”
Section: Introduction General Datamentioning
confidence: 99%